2021
DOI: 10.1093/cid/ciab943
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Viral Load Across the Spectrum of Untreated Human Immunodeficiency Virus Type 1 (HIV-1) Infection: A Cross-Sectional Multicenter Study

Abstract: Background The aim of this large multicenter study was to determine variations in cerebrospinal fluid (CSF) HIV-RNA in different phases of untreated HIV-1 infection and its associations with plasma HIV-RNA and other biomarkers. Methods Treatment naïve adults with available CSF HIV-RNA quantification were included and divided into groups representing significant disease phases. Plasma HIV-RNA, CSF white blood cell count (CSF W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
(36 reference statements)
0
25
0
1
Order By: Relevance
“…The elements in these two compartments interact, and more particularly, systemic HIV disease serves as the foundation for the CNS complications in several aspects. It establishes the conditions of immunosuppression and immune activation that underlie CNS vulnerability ( 37 40 ), and, more directly, supplies the key elements of neuropathogenesis, including HIV invasion and major blood-derived cells involved in CNS immune-inflammatory reactions. However, while CNS virus-immune interactions partially echo those occurring systemically, there are important differences, with the CNS interactions being highly compartmentalized despite these systemic origins ( 36 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The elements in these two compartments interact, and more particularly, systemic HIV disease serves as the foundation for the CNS complications in several aspects. It establishes the conditions of immunosuppression and immune activation that underlie CNS vulnerability ( 37 40 ), and, more directly, supplies the key elements of neuropathogenesis, including HIV invasion and major blood-derived cells involved in CNS immune-inflammatory reactions. However, while CNS virus-immune interactions partially echo those occurring systemically, there are important differences, with the CNS interactions being highly compartmentalized despite these systemic origins ( 36 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Among the viruses considered in this collection, HIV likely has the most complex and intimate interactions with the immune system and inflammatory responses, both outside (i.e., systemically) and within the CNS. In both systemic and CNS compartments these interactions change over the long course of chronic infection ( 36 , 37 ). Figure 1 diagrams these interactions, dividing the systemic (left) from CNS (right) processes.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…The prevalence of CSF viral escape may differ between studies depending on the overall ART status of the participants. For instance, one study done on ART-naïve individuals reported a prevalence of 13% (126/972) [ 19 ] while another study reported 29% (12/42) cases of CSF viral escape in ART-experienced participants [ 20 ]. Furthermore, CSF viral escape may differ in acute versus chronic HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…HIV‐1 infects the central nervous system (CNS) shortly after transmission during primary infection 1 and can cause risk of HIV‐associated dementia during its advanced stage of the disease several years later, if left untreated 2 . In general, HIV is detected in the cerebrospinal fluid (CSF) in individuals with and without neurologic symptoms during all stages of infection, although the CSF the viral load is often higher in patients with HIV‐associated dementia or CNS opportunistic infections causing meningeal inflammation 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 In general, HIV is detected in the cerebrospinal fluid (CSF) in individuals with and without neurologic symptoms during all stages of infection, although the CSF the viral load is often higher in patients with HIV-associated dementia or CNS opportunistic infections causing meningeal inflammation. 3 Chronic HIV infection causes progressive reduction in blood CD4+T-cell counts leading to immunosuppression and AIDS in a median of 10-11 years after primary infection. HIV-associated dementia and CNS opportunistic infections in general occur when CD4+ T cell counts fall below 200/mm 3 , that is, in patients with severe immunosuppression.…”
Section: Introductionmentioning
confidence: 99%